Evaluation of acceptability, safety and expulsion rate of PPIUCD - Chauhan, R.; Sahni, Sonal; Hanumantaiya, Shaily (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The modern intrauterine contraceptive device (IUCD) is highly effective, safe, private, long acting, coitus independent, rapidly reversible, cost effective and can be used by women who are breastfeeding. This study was conducted to evaluate factors associated with acceptability, safety and expulsion rates of PPIUCD among clients in the Department of Obstetrics and Gynecology, N. S. C. B Medical College, Jabalpur. Methods: A questionnaire based prospective study was conducted between March 2016 -17 on all the clients who were counseled for PPIUCD and who fulfilled the WHO Medical Eligibility criteria. Proforma included follow up at 6 weeks post-delivery. Results: In our study 961 women accepted PPIUCD (53.3%). Majority of the cases belonged to low socioeconomic group with low literacy rates. Most acceptors counseled in antenatal period (53.1%). Majority (67.3%) of insertions were post placental and instrumental (89%). At the time of insertion most clients experienced mild pain (49.7%) & anxiety (42.5%). Amongst clients who followed up (51.1%), the most common complaint was pain (16.7%) and most common reason for removal was heavy bleeding. Continuation rate was 77.7%, spontaneous expulsion in 9.75% while voluntarily removal was done in 12.6%. At follow up 91.3% clients were satisfied with PPIUCD. Conclusions: Antenatal counseling has a very important role. Demographic factors influencing acceptance are education, socioeconomic status and family structure. PPIUCD is demonstrably safe and effective method of contraception with low expulsion rate. Awareness about the safety and efficacy of PPIUCD should be emphasized during antenatal visits.